THE EFFECT OF TRANSFER PRICING AND SALES GROWTH ON TAX AVOIDANCE (EMPIRICAL STUDY OF TRADING COMPANIES LISTED ON THE IDX IN 2016-2021) - Alya Salsabila (Sean Institute, 2023)
This thesis discusses the effect of transfer pricing and sales growth on tax avoidance (an empirical study of trading companies listed on the IDX in 2016-2021). Tax is the main source of income for a country so that taxpayers must pay taxes in an orderly manner. For companies that have to pay taxes, taxes can reduce the profits that companies get, while the government has a desire to increase tax revenues as state revenue. Thus, this raises a tendency for taxpayers to minimize the overall tax payment through tax avoidance practices. The object of this research is a trading company listed on the Indonesia Stock Exchange (IDX) for the 2016-2021 period. The research results can be used as a reference in calculating and paying taxes so that tax avoidance does not occur by looking at transfer pricing, sales growth, leverage and company profitability.